The Influence of the Problem-Based Learning Model Assisted by Google Sites Interactive Multimedia on Critical Thinking Skills in the Science Subject of Grade V Elementary School - Pradana, Galih Yoga; Mariana , Neni; Anam , Rif’at Shafwatul (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
Critical thinking skills are part of 21st century learning that are important to be applied in the learning process. However, these skills have not been fully mastered by students. Based on the results of observations conducted in one elementary school, students have difficulty working on analytical questions. This study aims to determine the effect of the Problem-Based Learning model assisted by interactive multimedia Google sites significantly on critical thinking skills in the subject of science for grade V of elementary school. This type of research is a quasi-experiment with a nonequivalent control group design. The population in this study were grade V students of SDN 3 Bangunsari Ponorogo totaling 82 students. The research sample was grade V students consisting of a control class and an experimental class, each totaling 30 students. Data analysis used an independent sample t-test. The results showed that there was a difference in the average results of the pretest and posttest of critical thinking skills in the experimental class and the control class. In the experimental class there was an increase of 19.56%. While in the control class it increased by 6.27%. The results of the hypothesis test using the independent sample t-test showed a significance value (2-tailed) of 0.034, which means <0.05, thus Ho is rejected and Ha is accepted. So there is a significant influence of the Problem-Based Learning model assisted by interactive multimedia Google sites on critical thinking skills in the subject of science for grade V of Elementary School. Learning with the Problem-Based Learning model assisted by interactive multimedia Google sites has been proven to be able to improve students' critical thinking skills.